Largely enhanced electrical properties of polymer composites via the combined effect of volume exclusion and synergy. Issue 57 (27th May 2016) - Wu, Kai; Wu, Linyu; Yang, Weixing; Chai, Songgang; Chen, Feng; Fu, Qiang
Abstract : The core–shell structure of surface conductive SiO2 @rGO could result in enhanced electrical conductivity and EMI shielding effectiveness as due to both synergistic effect and volume exclusion effect. Abstract : It has been demonstrated that introducing another non-conductive particle into conductive filler filled composites could result in a better conductivity due to a volume exclusion effect. It was also reported that combining electrically conductive fillers with different geometric shapes and aspect ratio together could enhance the electrical conductivity due to the synergistic effect. To further explore these two effects on the electrical property enhancement, we firstly encapsulated neat silica (SiO2 ) with graphene oxide (GO) through electrostatic self-assembly to render SiO2 with surface conductivity. Then neat SiO2 or SiO2 @GO together with multi-walled carbon nanotubes (MWCNT) were mixed with polystyrene (PS) to prepare conductive composites. In this way, the volume exclusion effect in the PS/MWCNT/SiO2 system and combined effect of volume exclusion and synergy in the PS/MWCNT/SiO2 @rGO system could be investigated and compared. An obvious increased conductivity was observed only in the transition composition region for the PS/MWCNT/SiO2 system compared with the PS/MWCNT system. However, a largely enhanced conductivity was achieved through the composition region for the PS/MWCNT/SiO2 @rGO system compared with the PS/MWCNT/SiO2 system and PS/MWCNT, accompanied by great enhancement of the electromagnetic interference (EMI) shielding effectiveness. Given the SEM characterization and rheological properties, we attributed this obvious enhanced electrical property to both a volume exclusion effect and a synergistic effect.